2010
DOI: 10.22201/igeof.00167169p.2010.49.1.1473
|View full text |Cite
|
Sign up to set email alerts
|

The application of electrical methods in exploration for ground water resources in the River Malacatoya sub-basin, Nicaragua

Abstract: En el contexto del cambio climático global, Nicaragua está siendo fuertemente afectada, manifestándose en la marcada variación temporal de los parámetros climáticos e hidrométricos. Como consecuencia de estas variaciones, en una franja paralela al Océano Pacífico que se extiende desde el extremo NO del Gran Lago de Nicaragua (Cocibolca) hasta los Departamentos de Madriz y Nueva Segovia (frontera con Honduras); las precipitaciones han disminuido notablemente en la última década, provocando intensas sequías y ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A particularly challenging paradigm is the adaptation of a geophysical survey method with mathematical formulation based on isotropic and homogeneous media for use in highly anisotropic and heterogeneous media (Rubin and Hubbard, 2005). Even so, studies involving ERT surveys in a crystalline geological environment showed that the method is efficient in this kind of hydrogeological investigation (Okpoli, 2013;Sequeira Gómez & Escolero Fuentes, 2010;Moreira et al, 2016;Moreira et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A particularly challenging paradigm is the adaptation of a geophysical survey method with mathematical formulation based on isotropic and homogeneous media for use in highly anisotropic and heterogeneous media (Rubin and Hubbard, 2005). Even so, studies involving ERT surveys in a crystalline geological environment showed that the method is efficient in this kind of hydrogeological investigation (Okpoli, 2013;Sequeira Gómez & Escolero Fuentes, 2010;Moreira et al, 2016;Moreira et al, 2019).…”
Section: Introductionmentioning
confidence: 99%